(untitled) (Web of Technology: Multidimensional Research Journal, 2023)
This article examines pedagogical practice, the tasks of pedagogical practice of students, methods and tools, the quality and effectiveness of the educational process, mobile education, the creation of mobile applications and the possibilities of their use during the internship period.